Output-only structural identification of random vibrating systems - Mucheroni,Mário F. (2006)
A new form to carry out stochastic identification of structures in operational conditions using a non recursive method, the statistic analysis and the wavelet transform, is presented. The statistic analysis contributed to select the best system order and to automation of computational procedures. In general the identification of low frequencies is a difficult task. The wavelet transform is an essential tool for compression of data making possible the complete identification including low frequencies. In addition it improves the computational efficiency. The study of four degrees of freedom simulated system is presented and the results are compared with the analytical modal parameters.